2019
DOI: 10.1016/j.jcot.2018.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of patellar tendon versus hamstrings autografts for anterior cruciate ligament reconstruction in Indian population: A randomised control trial study

Abstract: Disruption of anterior cruciate ligament (ACL) is a common ligamentous injury of the knee. The best choice of graft for reconstruction remains undecided. This prospective, randomized clinical trial aimed to compare clinical results of bone-patellar tendon-bone (BPTB) grafts and four-strand semitendinosusgracilis (QHT) grafts for ACL reconstruction over a 1-year follow-up interval in Indian population. Methods: 42 consecutive patients with ACL injury were recruited, by pick and draw method and allotted into two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Of the 838 potentially relevant studies identified, 16 RCTs met the inclusion criteria [2, 3, 5, 10, 12, 16–18, 20, 22, 34–36, 41, 43, 46]. A PRISMA flow diagram is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 838 potentially relevant studies identified, 16 RCTs met the inclusion criteria [2, 3, 5, 10, 12, 16–18, 20, 22, 34–36, 41, 43, 46]. A PRISMA flow diagram is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the result only became significant if twice the number of events would have occurred. The included studies varied in this regard, with some requiring 3 times as many events to be reversed as events that occurred [12, 18]. This result is also independent of sample size since the ratio of the RFQ to the rate of rupture in each study population equals the ratio of the RFI to the number of events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11.-"In patients with a high level of intensity of pivoting sports practice, BPTB should be the favorite graft as an earlier graft ligamentization allows the implementation of a more aggressive rehabilitation program after surgery, and therefore a faster RTS in soccer" No consensus 69.2% BPTB autografts have been considered to have lower revision rates and higher postoperative stability than HT autografts and may be preferable in competitive high-level athletes in contact sports (77). Xie (78) suggested that BPTB autografts should be used in young and high-demand athletes to enable a greater proportion of patients to return to J o u r n a l P r e -p r o o f their preinjury sport postoperatively with higher levels of activity, but despite it provides better initial fixation and allows an early return, has been associated with different morbidities, such as anterior knee pain and loss of range of motion, and longer time to reach the Rh progression milestone than HS (29).…”
Section: No Consensus 692%mentioning
confidence: 99%
“…BPTB graft was once the gold standard due to the achieved bone-bone healing in the bone tunnels. Lately hamstring tendon is becoming the most common graft applied in the orthopaedic community [ [6] , [7] , [8] ] because significant complications such as donor pain, quadriceps atrophy and flexion contracture were reported in BPTB therapy [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%